Novel Intense-pulsed-light synthesis of amorphous SnO2 electron-selective layers for efficient planar MAPbI3 perovskite solar cells. (30th November 2021) - Oh, Kwonwoo; Jung, Kyungeun; Shin, Jaehak; Ko, Sunglim; Lee, Man-Jong
Highlights: The properties of amorphous-SnO2 treated with intense-pulsed-light (IPL) process are discussed. IPL irradiation eliminates surface −OH and enables the growth of a low-stress perovskite film. A PCE of 17.68% was achieved from a PSC based on the IPL-treated amorphous-SnO2 . Ultrafast processing time and undamaged obtained films brighten the future of IPL technology. Abstract: Although perovskite solar cells (PSCs) have achieved a high power conversion efficiency (PCE) within a short period of development, the high-temperature sintering of the constituent electron-selective layers (ESLs) impedes the commercialization. In this report, we demonstrate the effectiveness of an intense-pulsed-light (IPL) treatment for the rapid and damage-free sintering of amorphous-SnO2 ESLs for use in PSCs. The IPL treatment of amorphous-SnO2 substantially reduced the amount of surface hydroxyl groups, modified the surface energy, and enabled the growth of a low-stress perovskite layer with large grain sizes, all of which enhanced the photovoltaic properties and led to the proper alignment of band structures for efficient PSCs. Through comprehensive optimization of the IPL conditions, a PCE of 17.68% was achieved from the MAPbI3 planar PSC based on an amorphous-SnO2 IPL treated for a few tens of seconds, which was significantly increased compared with a PCE (7.06%) of nontreated SnO2 based counterpart. In addition, the PCE of the IPL-treated SnO2 based PSC is comparable to the best PCE (18.16%) of PSCs fabricated with SnO2 ESL annealed for three hours at 185 °C. Because of its ultrafast sintering time and tendency to not damage SnO2 ESLs, the new IPL process is expected to open new opportunities for the commercialization of PSCs. Graphical abstract: Image, graphical abstract